(untitled) - Khosrow-Pour, Mehdi (Hersley, PA, 2004)
Advanced Topics in Information Resources Management features the most current research findings in all aspects of information resources management. From successfully implementing technology change to understanding the human factors in IT utilization, this important volume addresses many of the managerial and organizational applications to and implications of information technology in organizations. Volume three will prove to be instrumental in the improvement and development of the theory and practice of information resources management while educating organizations on how they can benefit from and improve their information resources and all the tools utilized to gather, process, disseminate, and manage this valuable resource. *Note: This book is part of a new series entitled "Advanced Topics in "Information Resources Management". This book is Volume Three within this series (Vol. III, 2004).
Keywords: Information resources management,Information technology; Management